92 Establishing a satellite simulation suite on the neonatal intensive care unit. (30th November 2020) - Simpson, Gabrielle; Martinello, Kathryn; Gilbert, Amy
Abstract : Introduction: In situ simulation has long been considered the most favourable method of delivering immersive simulation. It allows candidates to rehearse clinical scenarios in a familiar environment and takes into consideration systems testing which can highlight potential latent safety threats. In situ simulation can further develop candidates' technical skills and contribute to team building and communication skills. In a high intensity environment such as neonatal intensive care (NICU), being prepared for rapid deterioration in acutely unwell patients is a necessity. Great Ormond Street Hospital NICU is a level 3 teaching unit with a high turnover of medical and nursing staff, and thus building key team working relationships can be challenging. Methods: A manikin from the Clinical Simulation Centre (CSC) was loaned to the NICU and a satellite simulation suite was established in a NICU cubicle. The manikin is stored in a portable cabinet to allow ease of movement throughout the unit. The suite was stocked with expired consumables to minimise waste and provide the necessary equipment needed for clinical scenarios. We developed a curriculum and regular weekly schedule factored into the unit's daily demands. This allows the clinical staff to pre-allocate candidates and ensures equal opportunities for clinical staff to attend. Results: We faced some challenges initially including identifying the ideal time and ensuring staff engagement. After overcoming these challenges, the programme has become well established. Staff are better engaged with the programme and timings are integrated into the unit's culture. Scenarios have been written to address patient safety incidents and identified knowledge gaps. Discussion: Despite facing initial challenges of staff engagement and incorporating the programme into the unit's culture, the satellite suite has been a huge success and has impacted on ward culture and patient safety.